9th company [videorecording (DVD)] - Bondarchuk, Fedor, 1967-; Bondarchuk, Fedor, 1967-; Chadov, Alekseĭ, 1981-; Evlanov, Mikhail; Kokorin, Ivan; Mikhalkov, Artëm, 1975-; Kri͡ukov, Konstantin, 1985- (WellGo USA, 2010)
The film is based on a true story of the 9th company during the Soviet invasion of Afghanistan in the 1980s. Young Soviet Army recruits are sent from boot camp directly into the war in Afghanistan. Real war is not like boot camp at all. This inexperienced company is sent to defend a difficult position, a task which may be beyond their capabilities.